Rural Poverty in Meghalaya : Nature, Dimensions and Possible Options - (:unkn) unknown (Planning Commission, 2001)
This summary examines rural poverty in Meghalaya, highlighting its persistent nature, socio-economic constraints, and potential policy solutions. With 30–55% of the rural population living below the poverty line, challenges include low agricultural productivity, unsustainable forestry practices, gender disparities, and political marginalization. Fiscal and administrative inefficiencies further hinder development, with a disproportionate share of state resources consumed by salaries and non-plan expenditures. The paper advocates a multifaceted approach involving local enterprise promotion, agricultural improvement, adaptive poverty alleviation schemes, sustainable forestry management, and enhanced governance. Structural reforms, timely fund allocation, and community participation are emphasized as critical for translating resources into meaningful socio-economic development, improving living conditions, and reducing poverty levels in the state.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Rural Poverty; Meghalaya; Agricultural Challenges; Forestry Management; Gender Inequality; Local Enterprise; Fiscal Constraints; Bureaucratic Inefficiency; Poverty Alleviation; Development Reforms